Expression of glycosylated proteins in bacterial system and purification by affinity chromatography - Breyer, Carlos Alexandre [UNESP]; de Oliveira, Marcos Antonio [UNESP]; Pessoa, Adalberto (Springer Nature, 2018)
The bacterial expression of glycoproteins has experienced significant progress in recent years, particularly in regard to the production of conjugate vaccines against pathogens. In this case, a protein carrier conjugated with glycosides is used to produce intense stimulation of the immune system. Glycoconjugate vaccines account for 35% of the global vaccine market, and consequently, several biotechnological companies have developed products for the purification of glycosylated proteins to attain homogeneity. In this chapter we present a general process for glycoprotein production in Escherichia coli and a practice method for purification of glycosylated proteins, using affinity chromatography.
Keywords: Affinity chromatography; Bacterial expression; Conjugate vaccines; Glycosylated protein